Plant Watering System Design Using Soil Moisture Automatic Sensor Microcontroller Based Sen0057 ATmega328P - Gani, Sitti Hardianti; Musa, Moh. Dahlan Th.; Nismayanti, Anis (Tadulako University, 2014)
It has been designed and created a plant watering system that is expected to help watering plants from a manual system to an automated system. The watering system is designed for watering plants at the right time and humidity. This tool utilizes SEN0057 soil moisture sensors to detect the level of soil moisture and ATmega328P microcontroller as the main controller. This tool is also used as a stop relay contact or disconnect from the current to flow to the pump, the LCD to display the time and the level of soil moisture and pump to drain the water. The working principle of this device when the sensor detects kelambaban ground level is less than the pre-defined limit, the microcontroller will command the process of watering until the soil moisture value equal to or greater than the pre-defined. Pepper plants as objects of research have suitable soil moisture ranging from 50% - 60%. Thus limits for soil moisture for plant watering is 3:38 volts. Watering the plant is operated at 5:45 pm and 17:45 pm.Keywords: Soil Moisture Sensor SEN0057, ATmega328P, Relays